Explainable AI in the Medical Field: A Survey on Machine Learning Interpretability and Use Cases - Thamer, Mahmood; N. Sultani, Zainab (Al-Nahrain Journal of Science, 2025)
Explainable Artificial Intelligence (XAI) is a branch of Artificial Intelligence (AI) that focuses on developing tools, methodologies, and algorithms capable of delivering interpretable, intuitively understandable insights and rationales for human users. The growing need for XAI in medicine and other fields stems from the increasing demand for equitable and ethical decision-making. It has been established that AI systems largely depends on historical data, therefore, any existing bias or behavior will be perpetuated. As such, deep examination and interpretation are required in this process. Since these black-box models lack transparency and interpretability, several XAI models are developed for the respective domains, ranging from healthcare, military, energy, finance, and industry.The highly sensitive areas, such as healthcare, require knowing the underlying principles of model predictions. Emphasizing feature importance, XAI has improved machine learning models to identify the most critical variables that help improve accuracy and efficiency. With the use of appropriate XAI techniques, actionable insights can be derived that would support informed decisions. In the healthcare sector, the primary objective of XAI is to provide clinicians with tools to effectively evaluate AI-generated data for better patient care. This survey covers Explainable AI, its methods, and their applications in the medical domain.